Comparative efficacy of Chinese herbal medicines for dialysis patients with uremic pruritus: A systematic review and network meta-analysis - Lu, Ping-Hsun; Lai, Chien-Cheng; Chiu, Ling-Ya; Wang, Jen-Yu; Lu, Po-Hsuan (Frontiers in Pharmacology, 2023)
Uremic pruritus is common in dialysis patients and reduces their quality of life. Chinese herbal medicine has been effective in patients with this condition. We conducted a random-effects network meta-analysis to compare the efficacies of different Chinese herbal medicine treatments for uremic pruritus. Outcome measures including the overall effective rates, visual analog scale scores, C-reactive protein levels, and adverse drug reactions were analyzed. The network meta-analysis retrieved 25 randomized controlled trials. Compared with conventional treatments alone, combination treatments with Xiao–Yang–Ke–Li was the most effective intervention in decreasing visual analog scale scores (mean difference −2.98, 95% mean difference −5.05 to −0.91) and levels of C-reactive protein (mean difference −5.01, 95% mean difference −7.27 to −2.75). Conventional treatment combined with Si-Wu Tang was superior to other therapeutic combinations when overall effective rates were determined. The best visual analog scale scores and overall effective rates were achieved by adjunctive treatment with the Touxie–Jiedu–Zhiyang decoction followed by uremic clearance granules; these treatments were the most beneficial for uremic pruritis. Our network meta-analysis provided the relative efficacies of different adjunctive Chinese herbal formulas. Adjunctive treatment with the Touxie–Jiedu–Zhiyang decoction was the best treatment for improving overall effective rates and reducing visual analog scores of uremic pruritus in dialysis patients.